BENTUK REPRESENTASI MATEMATIS SISWA DITINJAU DARI SELF-EFFICACY PADA MATERI KEKONGRUENAN DAN KESEBANGUNAN DI KELAS IXA - Rohmah, Afi Fatur; Mirza, Ade; Fitriawan, Dona (UNIVERSITAS TANJUNGPURA, 2023)
The poor performance of SMP Negeri 1 Binjai Hulu served as the inspiration for this study. students in solving math problems with an average score of 50.6 and still below the KKM which indicates that when solving math problems it is not optimal. The purpose of this study is to describe the form of mathematical representation of students at SMP Negeri 1 Binjai Hulu class IXA in solving problems of congruence and perpendicularity material in terms of Self-efficacy. The method used in this study is a qualitative method. The subjects in this study were 28 students of class IXA SMP Negeri 1 Binjai Hulu and 6 students to be interviewed. Data reduction, data presentation, and drawing conclusions are data analysis techniques that are used. The analysis of the data revealed that each student's responses to problems involving mathematical representation took different forms and included clues about issues with visual, verbal, and symbolic representation. Students with high self-efficacy are more optimal in answering questions, students with moderate self-efficacy have not maximized in using representation indicators so that there are some mistakes in solving problems, students with low self-efficacy as a whole have not achieved representation indicators well.